The Role of Readiness to Change between Transformational Leadership and Performance: Evidence from a Hospital during Covid-19 Pandemic - Dewiana Novitasari; Francisca Sestri Goestjahjanti; Masduki Asbari (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
The global competition in this era requires readiness, in particlar in this Covid-19 pandemic condition that is still surging in the world, including in Indonesia health sector. This study aimed to measure the effect of transformational leadership on employees’ performance of the employee of a hospital in Indonesia. Survey was done in one of the bussiets hosptial in greater Jakarta area using simple random sampling technique and the returned and valid questionnaire results were 154 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that transformational leadership have not significant effect on the employees’ performance, but transformational leadership have a positive and significant effect on readiness to change. Findings aslo revealed that readiness to change have a positive and significant effect on relationship between transformational leadership and employees’ performance. This study also confrimed that readiness to change as fully mediator. This new research proposed a model for building employees’ performance among the employee of a hospital in Indonesia through enhancing transformational leadership practice with readiness to change as a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.